Foam sclerotherapy of ulcus cruris venosum - Kahle, B. (Phlebologie, 2010)
The management of chronic venous leg ulcers is often sophisticated. The impact of pathophysiological findings of venous haemodynamics is relevant for the concept of the treatment in the individual subject. Thus elimination of reflux is thought to b relevant for the healing of venous leg ulcers. Mostly, patients with venous leg ulcers are elder persons with some relevant co-morbidities like diabetes, hypertension , cardiac or respiratory insufficiency.In many studies foam sclerotherapy (FS) has been shown to be an effective and safe procedure in the treatment of varicose veins. Therefore, FS plays an important role in the management of chronic venous leg ulcers in addition to compression therapy. We could demonstrate in a 18 patients that FS did not influence pulse rate and oxygen saturation. Very important is the aspect that FS can be performed effectively in patients under anticoagulation. The possibility to treat the patients in an outpatient setting with low costs and rapidly makes FS very attractive in comparison to alternative surgical techniques.
Keywords: Ulcus cruris venosum; foam sclerotherapy; anticoagulation